The Nature of Ferromagnetism in a System of Self-Ordered α-FeSi2 Nanorods on a Si(111)-4° Vicinal Surface: Experiment and Theory - Nikolay G. Galkin; Dmitrii L. Goroshko; Ivan A. Tkachenko; Aleksey Yu. Samardak; Konstantin N. Galkin; Evgenii Yu. Subbotin; Sergei A. Dotsenko; Dmitry B. Migas; Anton K. Gutakovskii (Nanomaterials, 2022)
In this study, the appearance of magnetic moments and ferromagnetism in nanostructures of non-magnetic materials based on silicon and transition metals (such as iron) was considered experimentally and theoretically. An analysis of the related literature shows that for a monolayer iron coating on a vicinal silicon surface with (111) orientation after solid-phase annealing at 450–550 °C, self-ordered two-dimensional islands of α-FeSi2 displaying superparamagnetic properties are formed. We studied the transition to ferromagnetic properties in a system of α-FeSi2 nanorods (NRs) in the temperature range of 2–300 K with an increase in the iron coverage to 5.22 monolayers. The structure of the NRs was verified along with distortions in their lattice parameters due to heteroepitaxial growth. The formation of single-domain grains in α-FeSi2 NRs with a cross-section of 6.6 × 30 nm2 was confirmed by low-temperature and field studies and FORC (first-order magnetization reversal curves) diagrams. A mechanism for maintaining ferromagnetic properties is proposed. Ab initio calculations in freestanding α-FeSi2 nanowires revealed the formation of magnetic moments for some surface Fe atoms only at specific facets. The difference in the averaged magnetic moments between theory and experiments can confirm the presence of possible contributions from defects on the surface of the NRs and in the bulk of the α-FeSi2 NR crystal lattice. The formed α-FeSi2 NRs with ferromagnetic properties up to 300 K are crucial for spintronic device development within planar silicon technology.